Mutagenic studies in a filamentous alga, employing a chemical mutagen–ethyl methane sulphonate - Aruna, M (Journal of Phytology, 2012)
The biological activity of certain chemical substances is referred to as radiomimetic because they produce all the biological effects observed after treatment with ionizing radiations (E.M.S) Ethyl Methane Sulphonate is a chemical mutagen which falls under the category of radiomimetic compound as it is a electrophilic alkylating agent which reacts with structures which are rich in electrons. An attempt has been made to study the effect of Ethyl Methane Sulphonate on the filaments of green alga, Cladophora crispata with varying percentage of concentrations ranging from 0.0001, 0.1 for duration of 1, 2 and 4 hours for a period of three weeks. Control samples were also maintained. Observations were recorded with reference to survival percentage, dry-weight, chlorophyll content, morphological and cytological variations.